THE TRANSFORMATION OF DIGITAL LITERACY IN INDONESIAN LANGUAGE LEARNING FOR PHARMACY STUDENTS: A STUDY ON THE USE OF INSTAGRAM AS A MULTILITERACY EVALUATION MEDIUM" - Verawati; Murtadho, Fathiaty; Utami, Sintowati Rini (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study explores the transformation of digital literacy in Indonesian language learning for pharmacy students through the integration of Instagram as a platform for multiliteracy-based evaluation. The research aims to develop an innovative pedagogical approach that aligns with the communicative and professional needs of pharmacy students while fostering their multiliteracy competencies. Employing a qualitative descriptive method, data were collected through observation, interviews, and content analysis of student-generated video assignments uploaded to Instagram. The findings reveal that the use of Instagram not only enhances students’ motivation and engagement but also enables authentic communication practices that bridge academic and digital contexts. Moreover, the platform supports multimodal expression and peer feedback, facilitating deeper reflection and learning. This research contributes to the field of Indonesian Language and Literature Education by proposing a contextual and technology-enhanced evaluation model that responds to the demands of 21st-century literacy practices, particularly in health-related disciplines. The study highlights the pedagogical potential of social media in fostering critical, digital, and disciplinary literacies through meaningful and interactive learning experiences.